E0487 One year outcome of transcatheter closure of very large atrial septal defect with amplatzer occluders. (17th November 2010) - Lianglong, Chen; Yukun, Luo; Chaogui, Lin; Yafei, Peng; Xingchun, Zheng
Abstract : Objective: This study was to investigate the outcome of transcatheter closuring large-to-huge ASD with the AOD within one year. Methods: 35 consecutive patients with large-to-huge ASD (330 mm) underwent transcatheter defect closure and then were followed up peri-procedurally, at 1-, 6-, and 12-month periods following the operation by clinical assessment, electrocardiographic and echocardiographic examination. All patients received 6-month anti-thromboembolic therapy by using either aspirin or warfarin at the discretion of the operator. The major adverse cardiac events (MACE) include cardiac death, occluder dislodgment leading to urgent cardiac surgery, occluder occupation significantly impeding haemodynamics or cardio-electrical activities, AOD-related thrombo-embolism, AOD-related atrial rupture, the minor adverse cardiac events (MACE) include occluder occupation with or without slight interference of haemodynamics, AOD-related arrhythmia and residual shunting. Results: The average diameter of ASD in 35 patients was 33.7±5.2 mm (range 30 mm to 38 mm), and the average diameter of final AOD used was 38.1±7.1 mm (range 32 mm to 42 mm). The immediate technical success was 100% without severe peri-procedural complications. MACE was not found in each stage within a one year follow-up, but MAC Ewas frequently encountered, among which occluder occupation with asympathetic haemodynamic interference occurred 45.7% peri-procedurally, 42.9% at 1-month, 40.0% at 6-month, and 34.3% at 12-month, and AOD-related atrial arrhythmia occurred 51.4% peri-procedurally, 14.3% at 1-month, 8.6% at 6-month, and 2.9% at 12-month. Persistent small residual shunting was found in 24 (68.6%) patients and I°AVB in one (2.9%) patient. Conclusions: The large-to-huge ASD can be occluded by using AOD without technical difficulty, but the long-term safety and efficacy requires further study.